The Influence of Financial Strategy, Operational Efficiency, and Financial Literacy on The Competitiveness of SMEs in Batu City - Maria Anita Adung; Retno Ayu Dewi Novitawati; Cakti Indra Gunawan (International Journal of Management and Business, 2026)
MSMEs are a crucial sector in the regional economy, absorbing labor and driving economic growth. In Batu City, MSMEs are growing rapidly, particularly in the food and beverage, crafts, and agro-tourism sectors. However, facing increasingly fierce competition, MSMEs are required to possess the skills to manage their businesses effectively and efficiently. This study aims to examine the influence of financial strategy, operational efficiency, and financial literacy on the competitiveness of Small and Medium Enterprises (SMEs) in Batu City. SMEs play a crucial role in the regional economy. However, in the face of increasingly intense business competition, effective financial strategy management, operational efficiency, and a strong level of financial literacy are essential to enhance business competitiveness. This study applies a quantitative approach with a causal associative research design, aiming to examine the cause-and-effect relationships between variables. The population in this study consists of 365 registered and active SMEs in Batu City. From this population, a sample of 78 SMEs was determined using the Slovin formula with a 10% margin of error and a purposive sampling technique. The data used are primary data obtained through the distribution of questionnaires with a Likert scale of 1–5. The data analysis technique uses multiple linear regression with the help of the SPSS program, and t-tests, F tests, and coefficients of determination (R²) are carried out. The results of the study indicate that financial strategy, operational efficiency, and financial literacy have a positive and significant effect on the competitiveness of SMEs, both partially and simultaneously. The significance value of each variable is less than 0.05. The F-test results show a significance value of 0.000 (<0.05), which means that all independent variables jointly influence the competitiveness of SMEs. The coefficient of determination (R²) value of 0.167 indicates that 16.7% of the variation in SME competitiveness can be explained by the variables of financial strategy, operational efficiency, and financial literacy, while the remainder is influenced by other factors outside the research model.